In vitro evaluation of carbendazim resistant Colletotrichum gloeosporioides isolates of grapes for sensitivity to QoI and DMI fungicides - INDU S. SAWANT*, SHUBHANGI P. NARKAR and (Indian Phytopathology, 2016)
Carbendazim is the only systemic fungicide recommended for anthracnose disease management in India, but its frequent use leads to increase in resistant strains compromising disease management. The present study was undertaken to find out carbendazim resistance in natural field population of Colletotrichum gloeosporioides, the causal agent of grape anthracnose. Three hundred and seventy nine isolates of C. gloeosporioides from the culture collection of ICAR-National Research Centre for Grapes, Pune, India, were screened for determining minimum inhibitory concentration (MIC) of carbendazim. Most of the isolates were found to be moderately resistant MIC, >10 - 1000 Âµg/ml; while only five isolates were sensitive to carbendazim with MIC value less than